Experiencias y vivencias en el manejo de procesos de interculturalidad desde el aula : caso de comunidad embera katío en Cali - Niño Agudelo, Natalia (Universidad de San Buenaventura - Cali, 2017)
In the present work, A descriptive research, tell the process of intercultural experiences in front of an indigenous community that lived El Calvario district in Cali. The proposal was born from a pedagogic practice lived in the CDI Alianza Cristiana located in the same neighborhood. The cause of this population that comes from Puerto Rico, Risaralda, was caused by the armed conflict, losing their homes and lands which made that migrated to Cali, the State was responsible for providing comprehensive care to the children of the indigenous community, between such education. It is there where this work focuses on how a western community makes the splice and achieves what we call intercultural processes. The teachers of this school we shared their experiences and how they worked this concept of intercultural.